Financing Risk Management in the Micro Business Unit of Bank Syariah Indonesia: A Case Study of the Parepare Branch - I Nyoman Budiono; Syahriayah Semaun; Andi Kiki Patmawati; Sri Sugiarti Salim; Nur Aisah Sari (Universitas Muhammadiyah Makassar, 2026)
Risk Management is a structured and systematic process of identifying, measuring, monitoring, controlling, and communicating risks in Islamic banks. This study, entitled